2007
DOI: 10.1002/meet.1450440357
|View full text |Cite
|
Sign up to set email alerts
|

User research and testing of FRBR prototype systems

Abstract: This study is part of a three-year ongoing IMLS-funded project on the research and development of FRBR-based retrieval systems to support user tasks and to facilitate effective information seeking. The major focus of this study is on user research and testing of current FRBR prototype systems. A sample of three such FRBR prototypes are evaluated and compared by 72 users from both public and academic library settings. This user study will help identify useful options for FRBR implementation and contribute towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They concluded that longer snippets enhanced performance on information tasks and reduced performance on navigational tasks. One study of a faceted search interface has incorporated a limited eye tracking protocol to identify interface elements looked at, but without examining detailed behavior (Zhang & Salaba, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that longer snippets enhanced performance on information tasks and reduced performance on navigational tasks. One study of a faceted search interface has incorporated a limited eye tracking protocol to identify interface elements looked at, but without examining detailed behavior (Zhang & Salaba, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eye tracking studies have been used to examine how users interact with general search results (Granka, Joachims & Gay, 2004; Lorigo et al, 2006; Pan et al, 2007); to evaluate specific web search design elements (Cutrell & Guan, 2007; Goldberg, Stimson, Lewenstein, Scott & Wichansky, 2002); and more recently in faceted search interfaces (Kules et al, 2009; Kules & Capra, submitted; Zhang & Salaba, 2007). Our previous studies have shown training and task‐related differences in how searchers attend to the facets and results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A three-year IMLS-funded project focused on how to effectively support user tasks and facilitate information seeking in developing FRBR-based systems. A portion of its study evaluated three FRBR prototypes based on user studies of 72 participants (Zhang and Salaba, 2008).…”
Section: Beyond the Opacmentioning
confidence: 99%